Mary Root and Susanne B. Wilson - Unknown:::Creator::::::::::::
Photograph shows Mary Root talking to Susanne B. Wilson next to a reception desk in the YWCA's Second Street building. In the background there is an old typewriter on the desk. The women are there for the 1973 YWCA annual meeting.